Intelligent security system - Zafar, Fairooz; Maliha, Maisha; Afnan, Moin (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.